Predation strongly limits demography of a keystone migratory herbivore in a recovering transfrontier ecosystem. Issue 10 (17th October 2022) - Watson, Fred; Becker, Matthew S.; Smit, Daan; Droge, Egil; Mukula, Teddy; Martens, Sandra; Mwaba, Shadrach; Christianson, David; Creel, Scott; Brennan, Angela; M'soka, Jassiel; Gaylard, Angela; et al.
Abstract: Large herbivore migrations are imperiled globally; however the factors limiting a population across its migratory range are typically poorly understood. Zambia's Greater Liuwa Ecosystem (GLE) contains one of the largest remaining blue wildebeest ( Connochaetes taurinus taurinus ) migrations, yet the population structure, vital rates, and limiting factors are virtually unknown. We conducted a long‐term demographic study of GLE wildebeest from 2012 to 2019 of 107 collared adult females and their calves, 7352 herd observations, 12 aerial population surveys, and concurrent carnivore studies. We applied methods of vital rate estimation and survival analysis within a Bayesian estimation framework. From herd composition observations, we estimated rates of fecundity, first‐year survival, and recruitment as 68%, 56%, and 38% respectively, with pronounced interannual variation. Similar rates were estimated from calf‐detections with collared cows. Adult survival rates declined steadily from 91% at age 2 years to 61% at age 10 years thereafter dropping more sharply to 2% at age 16 years. Predation, particularly by spotted hyena, was the predominant cause of death for all wildebeest ages and focused on older animals. Starvation only accounted for 0.8% of all unbiased known natural causes of death. Mortality risk differed substantially between wet and dry season ranges, reflecting strong spatio‐temporal differences in habitat and predator densities. There was substantial evidence that mortality risk to adults was 27% higher in the wet season, and strong evidence that it was 45% higher in the migratory range where predator density was highest. The estimated vital rates were internally consistent, predicting a stable population trajectory consistent with aerial estimates. From essentially zero knowledge of GLE wildebeest dynamics, this work provides vital rates, age structure, limiting factors, and a plausible mechanism for the migratory tendency, and a robust model‐based foundation to evaluate the effects of potential restrictions in migratory range, climate change, predator–prey dynamics, and poaching. Abstract : The paper provides the first quantitative characterization of the demography of the blue wildebeest population in western Zambia ‐ one of Africa's largest remaining migrations. Predation was the dominant cause of mortality, and mortality risk varied with position along the migratory route. This highlights the importance of protecting the migratory range of large herbivores.